Paleoseismic evidence of characteristic slip on the Western segment of the North anatolian fault, Turkey - Klinger, Yann (2012)
We have conducted a paleoseismic investigation of serial fault rupture at one site along the 110-km rupture of the North Anatolian fault that produced the Mw 7.4 earthquake of 17 August 1999. The benefit of using a recent rupture to compare serial ruptures lies in the fact that the location, magnitude, and slip vector of the most recent event are all very well documented. We wished to determine whether or not the previous few ruptures of the fault were similar to the recent one. We chose a site at a step-over between two major strike-slip traces, where the principal fault is a normal fault. Our two excavations across the 1999 rupture reveal fluvial sands and gravels with two colluvial wedges related to previous earthquakes. Each wedge is about 0.8 m thick. Considering the processes of collapse and subsequent diffusion that are responsible for the formation of a colluvial wedge, we suggest that the two paleoscarps were similar in height to the 1999 scarp. This similarity supports the concept of characteristic slip, at least for this location along the fault. Accelerator mass spectrometry (AMS) radiocarbon dates of 16 charcoal samples are consistent with the interpretation that these two paleoscarps formed during large historical events in 1509 and 1719. If this is correct, the most recent three ruptures at the site have occurred at 210- and 280-year intervals.